Successful treatment of a neonate with gastroschisis - Salazar Tito, Efraín (2023)
This is a newborn in the department of San Martín, who presented gastroschisis and was treated immediately with hydration, parenteral nutrition, decompression of the hollow viscera with aspiration and surgical technique, using a blood bag as a protector to then proceed to the continuous taxia and the daily washes; with good evolution and total suture on the seventh day after the operation.